Convex Probe Endobronchial Ultrasound - Bade, Brett; Furukawa, Brian; Tanner, Nichole T. (Seminars in Respiratory and Critical Care Medicine, 2014)
Convex probe endobronchial ultrasound (EBUS) is a minimally invasive diagnostic technique that allows real-time sampling of mediastinal and hilar lymph nodes and central pulmonary lesions. Its utility in diagnosing both malignant and nonmalignant diseases has led to an increased uptake and use by pulmonologists over the past decade. Because of the robust evidence supporting its safety and diagnostic yield, EBUS is now the first guideline recommended test for staging in non-small cell lung cancer (NSCLC). It has also a role in providing tissue for molecular analysis, thereby guiding in the selection of agents in the new era of personalized chemotherapies in the treatment of NSCLC. The following review highlights the evidence for EBUS in diagnosing mediastinal pathology and addresses technique, training, and competency and future directions for this technology.
Keywords: endobronchial ultrasound; lung cancer staging; mediastinal lymph node sampling